A method of analyzing the respective performances of hypothetical stirling engine and stirling cooler in Vuilleumier machine. (October 2020) - Zou, Peng; Gao, Qun; Wang, Shengli; Yang, Jiayao; Luo, Baojun; Hofbauer, Peter; Liu, Jingping; Huang, Yuexin; Ren, Chengqin
Abstract: The respective performances of hypothetical Stirling engine and Stirling cooler in Vuilleumier machines are usually unclear. In this paper, a method of alternate combination of adiabatic sub-model with considering the losses and isothermal sub-model without considering the losses was proposed. The engine's work output is obtained by combining adiabatic engine and isothermal cooler, while the cooler's work input is obtained by combining adiabatic cooler and isothermal engine. Then, engine's thermal efficiency and cooler's coefficient of performance (COP) were obtained. The relative Carnot efficiency of hypothetical engine was 45%–57% at conditions of 550 °C hot temperature and 50 °C–70 °C warm temperature. The relative Carnot efficiency of hypothetical cooler was 44%–51% at conditions of −20 °C~10 °C cold temperature and 50 °C~70 °C warm temperature. In addition, a comparison of Vuilleumier machines' COP based on a complete adiabatic model and the hybrid model was made. The ratio of COPV, hybrid over COPV, adia was in the range of 0.9~0.94. It indicated that the respective thermal efficiency and COPcooler in the hybrid model could approach to those in a complete adiabatic model.